(untitled) (Research, Society and Development, 2021)
Radiotherapy is one of the forms of cancer treatment and, although it is a method directed at tumor cells, it causes several damages to the oral cavity of patients diagnosed with head and neck cancer. Caries related to radiation, decreased salivation and the risk of osteoradionecrosis make the rehabilitative treatment of these patients quite challenging. Thus, the objective of this article is to report the clinical outcome of a post-radiation therapy patient due to cancer in the head and neck region who presented lack of retention and stability of the lower removable partial prosthesis due to the lack of support in function of coronary destruction by radiation-related caries. The rehabilitation was carried out with the preparation of a conventional upper denture and a lower overdenture prosthesis, using the dental roots of the lower canines as supports and use of precision restraint system. In general, the lower conventional full denture may have compromised retention and stability and in radiotherapy patients this condition is aggravated due to the consequences of radiotherapy in the oral cavity, directly affecting the masticatory, speech and aesthetic capacity, in addition to impacting in the patient’s quality of life. The risk of osteoradionecrosis may contraindicate the performance of extractions and installation of osteointegrated implants and therefore the maintenance of dental roots as a support for overdenture prostheses is an interesting alternative for the rehabilitation of these patients. Periodic follow-up of the radiotherapy patient is very important to avoid possible failures of the rehabilitation treatment.